2004
DOI: 10.1007/s00239-004-2673-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Complete Genome Sequence of Encephalitozoon cuniculi Supports the Fungal Origin of Microsporidia and Reveals a High Frequency of Fast-Evolving Genes

Abstract: Microsporidia are unicellular eukaryotes living as obligate intracellular parasites. Lacking mitochondria, they were initially considered as having diverged before the endosymbiosis at the origin of mitochondria. That microsporidia were primitively amitochondriate was first questioned by the discovery of microsporidial sequences homologous to genes encoding mitochondrial proteins and then refuted by the identification of remnants of mitochondria in their cytoplasm. Various molecular phylogenies also cast doubt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 63 publications
8
84
1
1
Order By: Relevance
“…The two expect values used, however, are too low to ensure the detection of short sequences and/or highly divergent orthologs due to the high rate of protein-sequence evolution in the microsporidian phylum 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two expect values used, however, are too low to ensure the detection of short sequences and/or highly divergent orthologs due to the high rate of protein-sequence evolution in the microsporidian phylum 20 .…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms are based only on DNA sequence information 19 and display high sensitivity but low specificity. In general, ab initio methods do not ensure small open reading frame identification, and their sensitivity is reduced for rapidly evolving sequences 18 , as shown for microsporidian gene sequences 20 . Despite substantial progress in the past decade, current gene identification methods are not able to produce an in extenso catalogue of protein-coding genes 17,[21][22][23] .…”
mentioning
confidence: 99%
“…The maximum-likelihood (ML; and Bayesian) methods have solved the long-branch attraction problem in theory (Felsenstein 1981), but not in practice: when the actual evolutionary process violates the underlying model of sequence evolution, consistency is no longer ensured, and fast-evolving lineages typically branch as sister groups (Lartillot & Philippe 2008). Recent studies of metazoan phylogeny (Philippe et al 2005), or of microsporidian origins ( Thomarat et al 2004), have revealed the existence and strong phylogenomic impact of such genome-wide fast evolving lineages. If the bias affects a majority of genes, then the reconstructed species tree will be wrong, and this will not be solved by adding new genes.…”
Section: Can We Still Recover the Species Tree?mentioning
confidence: 99%
“…One possible problem encountered in this study is the effect caused by the inequality of molecular evolutionary rate, commonly known as the "long branch artifact (LBA)" phenomenon, which can contribute to an incorrect tree topology (Philippe and Laurent, 1998). As several researchers have already pointed out (Hirt et al, 1999;Thomarat et al, 2004), microsporidian genes tend to exhibit a high rate of sequence divergence compared to those of typical eukaryotes. This observation suggests that it might be that microsporidian sequences artificially group together with fungal genes that represent another long 272 TANABE, WATANABE, and SUGIYAMA Vol.…”
Section: Did Microsporidia Evolve From Within the Fungi?mentioning
confidence: 99%